Bisphosphonate-related osteonecrosis of the jaws: legal liability from the perspective of the prescribing physician - Lo Russo, Lucio; Lo Muzio, Lorenzo; Buccelli, Claudio; Di Lorenzo, Pierpaolo (Journal of bone and mineral metabolism, 2013)
Recently, it has been reported that patients administered with bisphosphonates (BP), in particular cancer patients receiving intravenous amino-bisphosphonates, as well as patients taking oral BP for prevention/treatment of diseases of altered bone turnover, may be affected by a significant adverse reaction—BP-related osteonecrosis of the jaws (BRONJ). This condition may cause high morbidity and detriment of quality of life. Its treatment is complex and often unsatisfactory, and prevention strategies may have limited effectiveness, if any; thus, BRONJ may become a source of litigation in the near future. Although most cases seem to be triggered by invasive dental procedures and oral health care providers are more exposed to malpractice claims and legal actions pursuant to BRONJ, the attribution of liability requires caution. In fact, types of possible negligence claims against oral health care providers have already been highlighted. However, according to the medico-legal methodology, since BRONJ is an adverse reaction to BP administration, the attribution of liability, if any, requires a comprehensive consideration of the chain of events and figures acting before, and potentially related to BRONJ. The physician prescribing BP at the start of this chain has specific duties which we are going to address, and breaching these duties may set the stage for potential liability claims.